PENGEMBANGAN WEBTOON SEBAGAI MEDIA PEMBELAJARAN INTERAKTIF DALAM MENINGKATKAN KEMAMPUAN MENGAJAR MAHASISWA PADA MATA KULIAH MICRO TEACHING DI FAKULTAS EKONOMI UNIVERSITAS NEGERI PADANG - Menik Kurnia Siwi; Rita Syofyan; Annur Fitri Hayati (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2018)
This research aims to design and develop webtoon as an interactive learning media in improving students' teaching skills in micro teaching courses. This research is a research and development. This research is divided into two stages of workmanship. The first stage is webtoon design and development. The second stage is followed by the implementation of the use of webtoon as an interactive learning media in improving students' teaching skills in micro teaching courses.